The perpetual guest art in the unfinished present - Schwabsky, Barry (Verso, 2016)
"The idea of contemporary art sometimes allows us to pretend we have made a clean break with the past. In The Perpetual Guest, poet and critic Barry Schwabsky demonstrates that any robust understanding of art's present must also account for the ongoing life and changing fortunes of its past. In surveying the art world of this past decade, Schwabsky attends not only to its most significant newer faces--among them, Kara Walker, Thomas Hirschhorn, Ai Weiwei, Chris Ofili, and Lorna Simpson--but their forebears, both recent (Jeff Wall, Nancy Spero, Dan Graham, Cindy Sherman) and more distant (Velázquez, Manet, Matisse, and the portraitists of the Renaissance). "The art critic," Schwabsky writes, "formalizes and deliberately exemplifes the role of the spectator who realizes the artist's work, not by leaving it just as it is, but by adding something to it, making a personal contribution." Despite the hysterical pronouncements of criticism's demise, Schwabsky's rich and subtle considerations of art's complexly intertwined traditions are an indispensable contribution to understanding our present moment"-- Provided by publisher.